Water and Health - Singh, Prati Pal.; Sharma, Vinod; SpringerLink (Online service) (New Delhi : Springer India : Imprint: Springer, 2014)
(3z(BWater and Health(3y (Bstrengthens the dynamic relationship between human health and water. The book has the potential to ignite our minds about several water-related diseases due to biological and chemical contamination, and to their high-end solutions. The contents are original, comprehensive and highly informative, and gradually take the reader around the component most important to his or her quality life, and not just existence. The book is set in social, scientific and economic dimensions, and is a must read for all those who cherish and celebrate human life and dignity.s
1.Dengue: a water-related mosquito-borne disease -- 2.Water, environmental surveillance and molecular epidemiology of poliovirus in India -- 3.Hepatitis A and E in potable water: a threat to health -- 4.Waterborne viral gastroenteritis: an introduction to common agents -- 5.Cholera and drinking water -- 6.Typhoid fever and water -- 7.Shigellosis: an emerging water-related public health problem -- 8.Campylobacteriosis and water: an overview -- 9.Pathogenic mycobacteria and water -- 10.Water, mosquitoes and malaria -- 11.Water, amoebiasis and public health -- 12.Cyclosporiasis: an emerging potential threat for water contamination -- 13.Neurocycticercosis: an emerging waterborne parasitic disease of public health importance -- 14.Human cryptosporidiosis and drinking water: looking beyond HIV -- 15.Water and food borne trematodiases in humans -- 16.Water and lymphatic filariasis -- 17.Recent update on echinococcosis and water -- 18.Ascariasis and water: an overview -- 19.Soil-transmitted helminths and water.-Water and chemicals -- 20.Water quality issues needing technological interventions: sustainable availability for all -- 21.Pollution of aqueous matrices with pharmaceuticals.-22.Pesticide toxicity, water and health -- 23.Water quality and health issues in southwest parts of Punjab state, India -- 24.Groundwater chemical contamination: the implication for human health.
Keywords: Environmental sciences; Medicine; Microbiology; Waste disposal; Environment; Waste Management/Waste Technology; Medicine/Public Health, general; Popular Science in Medicine and Health; Microbiology